An Inventory of the Problems Related to Translating and Revising Legal Texts Issued by an African Court: A Case Study - Akpaca, Servais Martial (International Journal of Linguistics, Literature and Translation, 2020)
The aim of this paper is to make an inventory of the problems that translators encounter when they translate the documents issued by a specific African human rights court. More specifically translating at the ACHPR requires the knowledge of legal language and familiarity with a particular type of legal texts as well as competence in human rights conventions and charters and general translation skills. In an attempt to address these issues, this paper adopts a threefold approach, namely a historical approach recalling some legal systems and traditions upheld by courts, a theoretical approach throwing light on some key concepts and a lexical approach that makes it possible to extract legal terms from texts issued by the court and match them with their equivalents in the target language. The result of this research work is that legal translation is a specialised area due to the legal terms and systems involved in it. Unlike other specialised areas where the link between the signifier and the signified is fixed, in legal translation, the signified may be inflected due to differences between legal systems. Finding an equivalent for a legal term in another legal system or in a target language may beat times difficult and even impossible.